EKSEKUSI HAK TANGGUNGAN DI BANK SYARIAH (STUDI KASUS PUTUSAN NOMOR 5530/PDT.G/2017/PA.BADG) - Widodo, Syifa Esthiningtyas Putri; Setyorini, Dyah (Reformasi Hukum Trisakti, 2022)
The Mortgage Law and Objects Related to Land, namely Law Number 4 of 1996, (hereinafter reffered as the Mortgage Law) states that there are three ways if the debtor breaks a promise (wanprestasi) and the creditor can carry out the execution of the Mortgage object. The three methods consist of Parate Execution as stated in the Mortgage Law Article 6, Executorial Title as stated in the Mortgage Law Article 14 paragraphs (2) and (3), as well as Underhand Execution. Execution of Mortgage carried out by Islamic Banks in the Study of Decision Number 5530/Pdt.G/2017/PA.Badg remains subject to the Mortgage Law and the auction process which is carried out on the basis of Minister of Finance Regulation Number 27/PMK.06/2016 concerning The Instructions for Auction has been amended by The Minister of Finance Regulation Number 213/PMK.06/2020 concerning Instructions for Auction Implementation. The judge's considerations in adjudicating the Decision Number 5530/Pdt.G/2017/PA.Badg case are in accordance with the Mortgage Law, especially in Article 6 with the creditor still having the right to carry out execution through auction according to Minister of Finance Regulation Number 27/PMK. 06/2016 which has now been amended by Minister of Finance Regulation Number 213/PMK.06/2020.